Human papillomavirus infections among Hungarian female sex workers. (19th August 2013) - Marek, E.; Dergez, T.; D'cruz, G.; Bozsa, S.; Cseh, A.; Szilard, I.; Benczik, M.; Kiss, I.; Varszegi, D.; Vilagi, S.; Ember, I.; Gocze, P.
<x xml:space="preserve">Abstract</x> The purpose of this study was to assess the human papillomavirus (HPV) prevalence in cervical, oropharyngeal and anal samples of the high‐risk population of Hungarian female sex workers (FSWs). HPV testing of swab specimens from FSWs (n = 34) using polymerase chain reaction (PCR) methodology was performed. Results were compared with control group (n = 52) matched for age. Questionnaires were used to obtain data regarding participants' sexual behaviour. Data were analysed using SPSS. HPV DNA was detected in at least one location in a great majority of FSWs (82.4%), compared with 46.2% of the general female population (P < 0.05). Both the cervical and the anal samples of sex workers showed higher infection rates than those of controls (64.7% vs. 34.6% and 50.0% vs. 15.4%, respectively, P < 0.05). High‐risk HPV prevalence was also significantly higher in sex workers (55.9% vs. 25.0%, P < 0.05). A significantly higher proportion of FSWs had a history of genital warts (26.5% vs. 3.8%, P < 0.05). The results suggest that condom use may not result in adequate protection from HPV infection. The high infection rates among FSWs should be viewed as a priority group for HPV and cervical cancer prevention programmes since they are sources of HPV infection for the general population.